2012
DOI: 10.3177/jnsv.58.202
|View full text |Cite
|
Sign up to set email alerts
|

Puerarin Exerted Anti-Osteoporotic Action Independent of Estrogen Receptor-Mediated Pathway

Abstract: Summary Puerarin, a daidzein-8-C glucoside, is the major isoflavonoid in Kudzu ( Pueraria lobata ), and is unique in that it contains C-C conjugated glucose at position 8 of the isoflavonoid structure. A puerarin diet at a dose of 5 mg/kg b.w./d to fed ovariectomized mice for 2 mo diminished the urinary deoxypyridinoline, a typical bone-degradation product. Since the bone absorption marker, serum tartarate-resistant acid phosphatase (TRAP) activity of puerarin-fed mice decreased but the bone formation marker, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 21 publications
3
26
0
Order By: Relevance
“…Some preclinical in vivo and in vitro studies reported that puerarin was able to enhance new bone formation, [22][23][24] and prevent bone loss through an estrogen-like effect. 10,25,26) Consistent with their results, puerarin inhibited LPS-induced TRAP(+) MNCs formation in a dosedependent manner (Fig. 2), and the maximal concentration for inhibiting osteoclast formation at 50 µmol/L was higher than that of genistein (0.01-1 µmol/L) or daidzein (0.1-10 µmol/L) on osteoclastogenesis induced by TNF-α or RANKL in the same cells, respectively.…”
Section: Discussionsupporting
confidence: 74%
“…Some preclinical in vivo and in vitro studies reported that puerarin was able to enhance new bone formation, [22][23][24] and prevent bone loss through an estrogen-like effect. 10,25,26) Consistent with their results, puerarin inhibited LPS-induced TRAP(+) MNCs formation in a dosedependent manner (Fig. 2), and the maximal concentration for inhibiting osteoclast formation at 50 µmol/L was higher than that of genistein (0.01-1 µmol/L) or daidzein (0.1-10 µmol/L) on osteoclastogenesis induced by TNF-α or RANKL in the same cells, respectively.…”
Section: Discussionsupporting
confidence: 74%
“…Thus, PVEE and puerarin appeared to behave in a different manner to E2. We previously reported that puerarin did not bind to estrogen receptor a or b, while daidzein can bind to estrogen receptors (26). Therefore, the mechanism by which puerarin improved glucose metabolism probably does not involve estrogen-like activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, our previous experiments showed that uterine atrophy due to estrogen deficiency was unaltered by a puerarin-rich diet in OVX mice (7,40). Moreover, although the puerarin aglycone daidzein bound to estrogen receptors, puerarin did not bind estrogen receptors ␣ or ␤ (40).…”
Section: Discussionmentioning
confidence: 99%